Analyzing trends and future projections in fodder oats (Avena sativa L.) for quality seed production in India - Chand, Subhash; Kumar, Sanjay; Roy, Ajoy Kumar; Vijay, Dunna; Choudhary, Bishwa Bhaskar; Indu,; Kumar, Pradeep; Agrawal, Rajiv Kumar; Yadav, Vijay Kumar; Kaushal, Pankaj; Yadava, Devendra Kumar; Kumar, Ram Vinod; et al. (Frontiers in Plant Science, 2025)
Oats (Avena sativa L.) is a multipurpose, popular, nutritionally rich cereal crop widely used for food, feed, and fodder. In India, it is cultivated on nearly 0.25 M ha in the northern, northwestern, and central regions and has recently expanded to the eastern region, mainly for fodder purposes. Breeder seed (BS) production data were collected from the AICRP on Forage Crops and Utilization (FC&U) for a period of 24 years (1998–1999 to 2021–2022). Several fodder oat varieties have been developed and introduced into the seed chain in India over the past 24 years to suit different agro-climatic conditions. However, analysis reveals a narrow genetic base at the varietal level, with a few old and popular varieties (Kent, OS-6, and OS-7) sharing > 70% of the genome in varietal development. To encourage the cultivation of new varieties and replace older ones, adequate BS production is vital to ensure a regular supply of quality seeds for sustainable livestock production, providing nutritious and cost-effective fodder. With a few exceptions, the amount of BS indent and the number of varieties has increased, indicating growing demand and awareness of new varieties. At the institutional level, Indian Grassland and Fodder Research Institute (IGFRI) (Jhansi) contributed the highest to BS production (29.8%), followed by Punjab Agricultural University (PAU) (Ludhiana; 13.7%), AAU (Anand; 10.8%), and G.B. Pant University of Agriculture and Technology (GBPUAT) (Pantnagar; 9.9%). A moderate varietal replacement rate (22.9%) was observed for recently developed varieties (< 5 years) over the past 3 years (2019–2020 to 2021–2022). However, their contribution has significantly increased from 0.2% (2018–2019) to 26.2% (2021–2022). We estimated certified seed production (194,040 q) for 2023–2024 based on the available BS (485.1 q), assuming the seed chain operates at 100% efficiency. This production could cover 0.19 M ha of fodder oats in 2024–2025. The ARIMA model estimated that BS production and the number of varieties in the seed chain would reach 734.2 q and 28, respectively, by 2026–2027. Additionally, breeding approaches and improved management practices for enhanced seed production were discussed, and a roadmap was proposed to meet the demand for quality fodder oat seed in India.